1980
DOI: 10.1063/1.440148
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-17 NMR and EPR studies of water exchange from the first coordination sphere of gadolinium(III) aquoion and gadolinium(III) propylenediaminetetra-acetate

Abstract: The 17 0 NMR relaxation times, T, and T 2 , for water in aqueous solutions of Gd(CI0 4 )3 and GdPDTAand the EPR linewidths for the same complexes have been measured. These data are analyzed in terms of the Solomon-Bloembergen-Morgan equations for relaxation of a nucleus near a paramagnetic ion and McLachlan's theory for average EPR relaxation times. The analysis results in a consistent set of physical parameters for the electron relaxation as well as kinetic constants for the water exchange from the complexes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…17 O NMR studies of heme model compounds were reported by Momenteau and Gerothanassis [26,57,58] in the middle 1980s and on heme proteins and substrate binding to heme enzymes by Oldfield and collaborators [24,59,60]. 17 O NMR studies in the solid state were carried out by Oldfield and collaborators [61,62] in the middle 1980s, high pressure kinetics by Merbach and collaborators [63,64] in 1980s and protein hydration studies by Halle et al [29,65,66] in 1980s. Since the late 1990s, the unique potential of 17 O NMR has been demonstrated in its application to a great variety of chemical and biological problems ranging from hydration phenomena of biological macromolecules to studies of crystalline and amorphous materials, melts and high T c superconductors.…”
Section: Historical Perspectivementioning
confidence: 95%
“…17 O NMR studies of heme model compounds were reported by Momenteau and Gerothanassis [26,57,58] in the middle 1980s and on heme proteins and substrate binding to heme enzymes by Oldfield and collaborators [24,59,60]. 17 O NMR studies in the solid state were carried out by Oldfield and collaborators [61,62] in the middle 1980s, high pressure kinetics by Merbach and collaborators [63,64] in 1980s and protein hydration studies by Halle et al [29,65,66] in 1980s. Since the late 1990s, the unique potential of 17 O NMR has been demonstrated in its application to a great variety of chemical and biological problems ranging from hydration phenomena of biological macromolecules to studies of crystalline and amorphous materials, melts and high T c superconductors.…”
Section: Historical Perspectivementioning
confidence: 95%
“…Although the factors responsible for the linewidth of Gd(III) EPR spectra in aqueous solutions have been extensively studied and discussed in detail [87][88][89][90][91], the situation is complex, involving both inner-and outer-sphere exchange processes, together with dipole-dipole interactions, and effects due to transient distortions of complexes, factors which depend on both the symmetry and the number of coordinated water molecules. However, while the actual mechanism responsible for the slight increase in band width in the present case is not clear, the results are consistent with changes in the coordination sphere of the cation on binding to single stranded DNA or GTP.…”
Section: Electron Paramagnetic Resonance Studies (Epr)mentioning
confidence: 99%
“…Southwood-Jones et al [4] measured the temperature dependence of the I70-NMR relaxation rates of the complexes [Gd(H,0)8]3+ and [Gd (l) [S]. For the correct interpretation of these results, therefore, we would like to know the electronic relaxation rates of these complexes in solution over as wide a range of magnetic field as possible, particularly at high fields (for the NMR measurements the field was in the range 1.4 T to 9.4 T).…”
mentioning
confidence: 98%
“…We interpret the results using the idea of a transient zero-field splitting (ZFS) induced by distortion of the complexes. Such an interaction has been proposed to explain the larger than expected EPR line widths of a number of metal ions with spin S > 1/2 [lo-131, and has been successfully applied to a series of Gd3+ complexes [4] [14]. We will show, however, that some modification of the approach used to relate theory to experimental line widths will be necessary to explain the line width at high magnetic field, particularly for the polyaminocarboxylate chelates of interest in MRI that are presented here.…”
mentioning
confidence: 99%